THE IMPACT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY AT PT. TIRTA FRESINDO JAYA - Ikhsan Amar Jusman; Rohani Rohani (Sekolah Tinggi Pariwisata Mataram, 2021)
The research objective is to determine the influence of motivation and work environment at PT. Tirta Fresindo Jaya. There were 107 respondents as the sample of the study. The sampling technique is non-probability purposive sampling. Data collection used is observation, interviews and questionnaires. The data analysis used was the Normality Test, Multicolinearity Test, Heteroscedasticity Test, multiple linear regression analysis with data processing using SPSS version 22. The results proved that either partially or simultaneously, motivation and work environment had a positive and significant effect on increasing work productivity.